The Role of Hasanuddin Damrah in Education Development in South Bengkulu (1945 – 1968) - Wahyuni, Fadela Septi; Umasih, Umasih; Ibrahim, Nurzengky (Budapest International Research and Critics University, 2022)
Post-independence education changed following the ideals of Indonesian based on the 1945 Constitution. At this time, the emphasis of education was on nationalization and democracy. Thus, todays Indonesia need educators who suit by the ideals of Indonesian education that are democratic and nationalist. As a result, there is emergence of educator in various regions. This study aimed to determine the role of Hasanuddin Damrah in the education development of South Bengkulu Regency. This research uses a historical approach. The steps in this research initiate with topic selection, source collection, verification (external criticism and internal criticism), interpretation (analysis and synthesis). The result of this research show that the role played by Hasanuddin Damrah in advancing education in South Bengkulu has yielded good results. It is starting with his line of business, build the first secondary school in South Bengkulu, called Manna Middle School (SMP Negeri 1 Bengkulu Selatan), and build Manna High School (SMAN 1 Bengkulu Selatan), SMEP (first economic management school), SKP (first school of expertise). Moreover, his nationalist thinking by the ideals of education made him develop education in South Bengkulu which can be felt today.